DIMENSI PELAYANAN DALAM MEMBENTUK KEPUASAN DAN CITRA POSITIF PASIEN PADA PUSKESMAS DI KABUPATEN KUANTAN SINGINGI - Febri, Beri; Furwanti, Alvi; Hendriani, Susi (Jurnal Tepak Manajemen Bisnis, 2018)
Health services is one of the needs of the community, so now manyemerging businesses to meet these needs, whether committed by the organizationor personally, or by the government. One of them is Puskesmas (community healthcenter) owned by local government respectively. As a provider of non-profithealth services, making the existing services in the health center is sometimes notmaximal, so the public satisfaction becomes not optimal as well. Ultimately it willprovide a negative public outlook towards the Puskesmas. The purpose of thisstudy is to analyze the dimensions of service in forming satisfaction and positiveimage of patients at health centers in Kuantan Singingi Regency. This researchwas conducted in Kuantan Singingi Regency with the sample used is 170respondents who have been treated at puskesmas. Techniques Data collectionused is a questionnaire with Likert scale. SEM analysis is a hypothesis testing toolusing SmartPLS 4.0 and SPSS 17.00 for windows program. Result of research,there is influence of service dimension in forming satisfaction and positive imageof patient at puskesmas in Kuantan Singingi Regency. While empathy variable hasno influence to satisfaction and image of organization. In addition, responsivenessalso does not affect the image of the organization. The results of this studyprovide managerial implications, namely puskesmas must always improve thequality of services provided to patients, so as to be able to provide satisfactionand improve the image of puskesmas in the community.